Features of Investment Cooperation Towards in the Great Silk Road (Journal of Economic Research & Business Administration, 2018)
The investment cooperation between Kazakhstan and China provides the results for interacting parties.For Kazakhstan, the result of investment cooperation with China should contribute to a continuingsustainable economic growth, modernization of the domestic economy with the participation in the systemof world relations, for China it is a solution to the problem of preservation of sustainable economicdevelopment.For China, investment and economic cooperation in the project “One Let us explain oneway” identifies opportunities in expanding markets, the further development of export potential. Securingthe position of China in Kazakhstan’s economy – the broadening and deepening of trade andeconomic cooperation within the economic zone of New Silk Road.The existing commodity structureof imports determined the unrealized potential for strengthening relations with countries, consisting inthe development of machine-building, chemical, agro-industrial complexes, and the food industry. Theeconomy of most countries of the Silk Road has a commodity orientation and to achieve the goal of increasingthe competitiveness of national economies, strengthening the position in the international divisionof labor, they should gradually change their specialization towards intercountry cooperation, orientthe economy towards innovation development, and implement interstate innovative projects. The developmentof transport and logistics services, the creation of modern transport corridors will significantlyreduce the time of transportation of raw materials, semi-finished products and finished products, reducetransport costs, lead to a reduction in production costs and will affect the competitiveness of goods.